HUBUNGAN ANTARA RESILIENSI DENGAN TINGKAT KECEMASAN PASIEN KANKER DI RSUD PANEMBAHAN SENOPATI BANTUL YOGYAKARTA - Agus Sarwo Prayogi; sugeng jitowiyono; Igusti ayu agung ardianti (FORIKES, 2016)
Background: Cancer is a disease with term mortality second highest taxable income of heart disease in the world. A total of 68.638 in case cancer was found in 2013 in Central Java, Yogyakarta found 4.1% per 1,000 case of cancer, and in Hospital Panembahan Senopati on January there were 282 cases. The process of chemotherapy cause psychological problems for patients is anxiety. Anxiety usually occurred because a person's lack of ability to adapt in the face of adversity or can be called with resilience. Objective: To determine the corelation between resilience with anxiety levels of cancer patients in hospitals Panembahan Senopati, Bantul, Yogyakarta. Methods: The methods of this research used a correlation of descriptive with cross-sectional design consisting of the 75 respondents using purposive sampling technique. Variable dependent resilience, variable independent anxiety levels of cancer patients. Results: There between correlations resilience with anxiety levels of patients cancer in hospitals Panembahan Senopati Bantul, with findings Kendall Tau test at -0231 and Zhitung obtained 2.904265 by the P value of 0.027 (P